Coordinated response of Au-NPs/rGO modified electroactive biofilms under phenolic compounds shock: Comprehensive analysis from architecture, composition, and activity. (1st February 2021) - Li, Biao; Sun, Jia-Dong; Tang, Chen; Zhou, Jun; Wu, Xia-Yuan; Jia, Hong-Hua; Wei, Ping; Zhang, Yi-Feng; Yong, Xiao-Yu
Highlights: In-situ Au-NPs/rGO modification enhanced EAB's power density by 28.66–42.82%. EABs activity can be regulated by phenolic compounds with a "boundary". EABs showed heterogeneity in structure, composition, and activity under the shock. EPS play a vital role in balancing EET and cells protection. Abstract: Electroactive biofilms (EABs) can be integrated with conductive nanomaterials to boost extracellular electron transfer (EET) for achieving efficient waste treatment and energy conversion in bioelectrochemical systems. However, the in situ nanomaterial-modified EABs of mixed-culture, and their response under environmental stress are rarely revealed. Here, two nanocatalyst-decorated EABs were established by self-assembled Au nanoparticles-reduced graphene oxide (Au-NPs/rGO) in mixed-biofilms with different maturities, then their multi-property were analyzed under long-term phenolic shock. Results showed that the power density of Au-NPs/rGO decorated EABs was significantly enhanced by 28.66–42.82% due to the intensified EET pathways inside biofilms. Meanwhile, the electrochemical and catalytic performance of EABs were controllably regulated by 0.3–3.0 g/L phenolic compounds, which, however, resulted in differential alterations in their architecture, composition, and viability. EABs originated with higher maturity displayed more compact structure, lower thickness (110 μm), higher biomass (8.67 mg/cm 2 ) and viability (0.85–0.91), endowing it better antishock ability to phenolic compounds. Phenolic-shock also induced the heterogeneous distribution of extracellular polymeric substances in terms of both spatial and bonding degrees of the decorated EABs, which could be regarded as an active response to strike a balance between self-protection and EET under environmental pressure. Our findings provide a broader understanding of microbe-electrode interactions in the micro-ecology interface and improve their performance in the removal of complex contaminants for sustainable remediation and new-energy development. Graphical abstract: Image, graphical abstract